PENGARUH MEKANISME TATA KELOLA PERUSAHAAN TERHADAP KONSERVATISME AKUNTANSI: STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2021-2024 - Luh Candri, Jwalita; Goretti Kentris Indarti, Maria (Penerbit Lafadz Jaya, 2025)
This study aims to analyze the impact of managerial ownership, institutional ownership, independent commissioners, and audit committees on accounting conservatism mechanisms in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2021-2024. Accounting conservatism is a fundamental principle in financial reporting that helps mitigate the risk of overstating income and assets. The study applies a quantitative approach using secondary data derived from company financial reports. A total of 114 manufacturing firms consistently listed during the study period were selected using purposive sampling. The results show that managerial ownership and institutional ownership have a significant negative effect, while independent commissioners and audit committees have a significant positive effect. This research suggests enhancing the involvement of managerial and institutional shareholders by improving their monitoring roles, along with reinforcing the supervisory responsibilities of audit committees and independent commissioners to promote accounting conservatism.